Pengaruh Indian Ocean Dipole (IOD) Terhadap Produksi Penangkapan Ikan Lemuru (Sardinella lemuru) di Perairan Selat Bali - I Dewa Gede Alit Sujana; I Dewa Nyoman Nurweda Putra; Ni Luh Ria Puspitha (Journal of Marine and Aquatic Sciences, 2020)
Indonesia is one of tropical country which is very vulnerable to extreme phenomena in its water, such as Indian Ocean Phenomena (IOD) that occurred in Indian Ocean. The Bali Strait is directly adjacent to the Indian Ocean in the south area. Bali Strait is a region in Indonesia that has a high potential fishery resources namely, lemuru (Sardinella lemuru). The purpose of this study is to observe correlation and influence of IOD on lemuru production in Bali Strait between 2012 - 2016. The data used in this research are lemuru data was collected from 3 fish landing base namely PPP Muncar, PPN Pengambengan and PPI Kedonganan and IOD data used Dipole Mode Index (DMI) monthly from 2012 – 2016. The calculation used correlation equation, regression of second order polynomial. The highest lemuru production during 5 years, from 2012 untill 2016 was in 2015, accounted of 27,144,784 kg and the lowest production was in 2012 accounted of 5,644,146 kg. Based on that results, the highest yield of lemuru in the transition period II (September - November) of 31,938,833 kg with an average yield of 2,129,256 kg and the lowest was in east season (June - August) of 9,216,230 with average yield of 614,415 kg. The influence of IOD Index with lemuru production in Bali Strait has a determination value (R2) of 0.0558 and has a correlation of 17.40% with a positive influence (directly proportional). It was categorized as very weak.